2017
DOI: 10.1371/journal.pone.0181075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms by which casein glycomacropeptide maintains internal homeostasis in mice with experimental ulcerative colitis

Abstract: ObjectivesThe aim of this study was to elucidate the molecular mechanisms by which food-derived casein glycomacropeptide (CGMP) maintains internal homeostasis in the intestinal mucosa and to investigate the effects of CGMP on the intestinal mucosal immunological barrier and related signal transduction pathways.MethodsIn this study, a famoxadone (OXZ)-induced mouse experimental ulcerative colitis (UC) model was built. The experimental UC mice were intragastrically administered milk-derived CGMP for four consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Although we did not perform permeability assays, we believe that the inhibitory effect of GMP on IL-1β and TNF-α expression and the up-regulation of TGF-β at the intestine of FA animals may prevent an impaired intestinal barrier function, as it has been demonstrated with in vitro studies using cell lines of enterocytes and goblet cells [ 81 , 82 ]. This suggestion is supported by studies showing that GMP is able to inhibit signaling pathways involved in TNF-α and IL-1β gene expression, such as NF-κB and MAPK pathways, in the intestinal mucosa of mice with ulcerative colitis [ 83 ], as well as in cell lines of goblet cells [ 81 ], mature enterocytes [ 84 ], and macrophages [ 85 ]. Future research in this field will be necessary to demonstrate it.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although we did not perform permeability assays, we believe that the inhibitory effect of GMP on IL-1β and TNF-α expression and the up-regulation of TGF-β at the intestine of FA animals may prevent an impaired intestinal barrier function, as it has been demonstrated with in vitro studies using cell lines of enterocytes and goblet cells [ 81 , 82 ]. This suggestion is supported by studies showing that GMP is able to inhibit signaling pathways involved in TNF-α and IL-1β gene expression, such as NF-κB and MAPK pathways, in the intestinal mucosa of mice with ulcerative colitis [ 83 ], as well as in cell lines of goblet cells [ 81 ], mature enterocytes [ 84 ], and macrophages [ 85 ]. Future research in this field will be necessary to demonstrate it.…”
Section: Discussionmentioning
confidence: 90%
“…IgA expression in intestinal tissue of FA animals administered with GMP showed a strong tendency to increase. Accordingly, in an experimental model of ulcerative colitis, GMP intake recovers the levels of secretory IgA in intestinal mucosa of mice and potentiates the anti-inflammatory signal transduction mediated by TGF-β [ 83 ]. GMP administration also results in an increased number of IgA-positive plasma cells in the intestinal lamina propria of healthy animals [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster of differentiation 1a acts as an inflammatory mediator of UC, inducing T cell activation to elicit an immune response in the body ( 52 ). As a central factor in immune mediation, the elevated levels of secretory IgA in the colon help to prevent intestinal damage and restore mucosal barrier function ( 53 ). IgG exerts important protective and regulatory effects in the placental barrier ( 54 ) and IgM serves an important role in its own immune regulation ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, a recent study demonstrated that oral GMP administration to mice resulted in a greater number of IgA-positive plasma cells in the intestinal lamina propria [74]. Accordingly, other work showed that GMP intake recovers the levels of secretory IgA in intestinal mucosa of mice with experimental ulcerative colitis [75]. Altogether, these results suggest an immuno-suppressing activity of GMP on systemic humoral response, but an immuno-stimulating activity on humoral mucosal immunity.…”
Section: Gmp Biological Activitiesmentioning
confidence: 87%
“…Authors concluded that the intestinal anti-inflammatory action of GMP is probably mediated by the direct modulation of monocyte or splenocyte activity, especially by hampering the activation of T helper 1 (Th1) cells while favoring the differentiation of regulatory T (Treg) cells [68]. In the same way, in a mice model of famoxadone-induced colitis, orally GMP induced body weight restoration and intestinal injury reduction, in association with a decrease in CD4, CD8, mucosal addressin cell adhesion molecule-1 (MAdCAM), mitogen extracellular-signal-regulated kinase kinase-1 (MEKK1), and Smad7 (a molecule that transduces TGF-β signaling) intestinal expression [75]. Thus, GMP protection in colitis might be due to a decrease in T-lymphocyte gut infiltration, and to an upregulation of TGF-β and a downregulation of mitogen activation protein (MAP) kinase and NF-κB signaling pathways.…”
Section: Gmp Biological Activitiesmentioning
confidence: 99%